2013
DOI: 10.1016/j.juro.2013.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Renal Pelvic Dilatation for Detecting Surgically Managed Ureteropelvic Junction Obstruction

Abstract: Our findings suggest that the combination of fetal and postnatal renal pelvic dilatation is able to increase the diagnostic accuracy for detecting infants who need a more comprehensive postnatal investigation for upper urinary tract obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 30 publications
0
40
0
1
Order By: Relevance
“…Another study found that only 2% had fUTI and 1% had surgery if postnatal APD was 5–14 mm 33. No threshold was given by Dias et al ,34 35 even though they reported that postnatal APD was better for detecting the need of pyleoplasty than the Society for Fetal Urology grading system,35 and that risk of dilated VUR increased with postnatal APD >10 mm 34. According to our criteria for performing VCUG, some VUR cases without dilated ureters on US, no fUTI and normal kidney function may be classified as hydronephrosis in our study.…”
Section: Discussionmentioning
confidence: 98%
“…Another study found that only 2% had fUTI and 1% had surgery if postnatal APD was 5–14 mm 33. No threshold was given by Dias et al ,34 35 even though they reported that postnatal APD was better for detecting the need of pyleoplasty than the Society for Fetal Urology grading system,35 and that risk of dilated VUR increased with postnatal APD >10 mm 34. According to our criteria for performing VCUG, some VUR cases without dilated ureters on US, no fUTI and normal kidney function may be classified as hydronephrosis in our study.…”
Section: Discussionmentioning
confidence: 98%
“…VUR rates among patients with mild, moderate, and severe prenatal HN are not significantly different (14). Similarly, Dias et al have shown that if prenatal APD is >18 mm in the 3 rd trimester and >16 mm postnatally, the sensitivity and specificity of these cut-off values to identify infants who would eventually require pyeloplasty for UPJO were 100% and 86%, respectively (17).…”
Section: Cuaj -Cua Guideline Capolicchio Et Al Guideline: Antenatallymentioning
confidence: 93%
“…Whereas there is no complete consensus about the best definition and grading system for pyelectasis, measurement of the anterior–posterior diameter (APD) of the renal pelvis in the transverse plane is the standard approach for diagnosis [145]. An APD of >15 mm is strongly predictive of uretero-pelvic junction obstruction [146]. However, APD is affected by multiple factors, including gestational age and maternal hydration status (and hence fetal urine output), and may worsen or improve during later development [147].…”
Section: Antenatal Diagnosis Of Renal Pathologymentioning
confidence: 99%